The Effect of Environmental Management and Sustainability on Destination Image and Tourist Revisits at Tourism Destinations in Bandung - Budi Utama, Ahmad Nur; Silamat, Eddy; Lesmana, Tera (Westscience Press, 2024)
This study investigates the impact of environmental management and sustainability practices on the destination image and tourist revisit intentions at tourism destinations in Bandung City. Employing a quantitative research design, data were collected from 160 tourists using a Likert scale survey. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was utilized for data analysis. The findings reveal that both environmental management and sustainability practices positively influence destination image, which in turn significantly affects tourists' intentions to revisit. Notably, sustainability practices have a stronger impact on both destination image and revisit intentions compared to environmental management alone. These results underscore the importance of integrating comprehensive sustainability strategies into tourism planning to enhance destination competitiveness and attract environmentally conscious tourists. The study provides practical insights for tourism managers and policymakers aiming to foster sustainable tourism growth in Bandung City.